The Involvement of Cholinergic Neurons in the Spreading of Tau Pathology - Simon, Diana; Hernandez, Felix; Avila, Jesus (Frontiers in Neurology, 2013)
Long time ago, it was described the selective loss of cholinergic neurons during the development of Alzheimer disease. Recently, it has been suggested that tau protein may play a role in that loss of cholinergic neurons through a mechanism involving the interaction of extracellular tau with M1/M3 muscarinic receptors present in the cholinergic neurons. This interaction between tau and muscarinic receptors may be a way, although not the only one, to explain the spreading of tau pathology occurring in Alzheimer disease.